Efektivitas Business to Business Marketing dalam Meningkatkan Jangkauan Pasar Batik Cibuluh, Bogor - Anggini, Karlita; Carissa, Dhea Cindy; Rafiqah, Rafiqah; Putra, Rafiadi Parwedi; Ramadhani, Hanif Fadila; Ayyubi, Salahuddin El (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The Business-to-Business marketing (B2B marketing) program in Kampung Batik Cibuluh was implemented by the IPB Capstone Team from September to November 2024. This program aims to improve B2B marketing skills, expand collaboration networks, and empower the local economy through mentoring nine Cibuluh batik groups involving 40 craftsmen. The program implementation was carried out through the stages of preparation, socialization of B2B marketing concepts, designing B2B marketing strategies, offering to potential partners, and monitoring and evaluation. The evaluation results showed that the program was in accordance with the needs of the partners, succeeded in increasing the craftsmen's knowledge of B2B marketing strategies, built the craftsmen's confidence in establishing business cooperation, and produced quality promotional media. In addition, this program has the potential to increase sales of batik products. Overall, the implementation of B2B marketing strategy proved to be effective in expanding the market reach of Cibuluh Batik products.